2018
DOI: 10.1021/acs.jafc.7b05575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Sterols or β-Cryptoxanthin at Physiological Serum Concentrations on Suicidal Erythrocyte Death

Abstract: The eryptotic and hemolytic effects of a phytosterol (PS) mixture (β-sitosterol, campesterol, stigmasterol) or β-cryptoxanthin (β-Cx) at physiological serum concentration and their effect against oxidative stress induced by tert-butylhydroperoxide (tBOOH) (75 and 300 μM) were evaluated. β-Cryptoxanthin produced an increase in eryptotic cells, cell volume, hemolysis, and glutathione depletion (GSH) without ROS overproduction and intracellular Ca influx. Co-incubation of both bioactive compounds protected agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Furthermore, these authors indicated the alteration of erythrocytes morphology with an increase in stomatocytes (increased volume potentially linked with hemolysis) and spherocytes (associated with reduced pliability and osmotic fragility) (Sikdar et al, 2017). Moreover, we have previously reported ex vivo that tert-butylhydroperoxide induced oxidative stress in erythrocytes resulted in two cell populations, with low size (FSC < 20, associated with eryptosis) and big size (FSC > 80, associated with a preliminary step of hemolysis) (Álvarez-Sala et al, 2018). In line with this, we have shown in the present study a marginal increase (non significant trend) of FSC (higher cell volume) in erythrocytes from smokers to be possibly ascribed to the presence of high quantities of stomatocytes.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, these authors indicated the alteration of erythrocytes morphology with an increase in stomatocytes (increased volume potentially linked with hemolysis) and spherocytes (associated with reduced pliability and osmotic fragility) (Sikdar et al, 2017). Moreover, we have previously reported ex vivo that tert-butylhydroperoxide induced oxidative stress in erythrocytes resulted in two cell populations, with low size (FSC < 20, associated with eryptosis) and big size (FSC > 80, associated with a preliminary step of hemolysis) (Álvarez-Sala et al, 2018). In line with this, we have shown in the present study a marginal increase (non significant trend) of FSC (higher cell volume) in erythrocytes from smokers to be possibly ascribed to the presence of high quantities of stomatocytes.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, according to the geo mean values derived from FSC (Fig. 1B), a growing trend of cell volume was observed in smokers compared to non-smokers (554.30 ± 32.31 vs. 536.30 ± 30.76 tvalue: 1.8260; p-value: 0.0756), possibly due to changes in morphology associated with preliminary steps of hemolysis (Álvarez-Sala et al, 2018). Representative histograms of Annexin V-binding and FSC of erythrocytes from one non-smoker and one smoker volunteer are also shown ( Fig.…”
Section: Eryptotic Status Of Circulating Erythrocytesmentioning
confidence: 91%
See 2 more Smart Citations
“…The process of eryptosis is characterized by cell membrane scrambling leading to breakdown of the cell membrane asymmetry and translocation of phosphatidylserine from the interior to the cell membrane surface . The cell membrane scrambling is typically paralleled by erythrocyte shrinkage and by the formation of blebs on the erythrocyte surface.…”
Section: Introductionmentioning
confidence: 99%